Real-life prognosis of 5041 bone-only metastatic breast cancer patients in the multicenter national observational ESME program. (January 2021) - Bertho, Marion; Fraisse, Julien; Patsouris, Anne; Cottu, Paul; Arnedos, Monica; Pérol, David; Jaffré, Anne; Goncalves, Anthony; Lebitasy, Marie-Paule; D'Hondt, Véronique; Dalenc, Florence; Ferrero, Jean-Marc; et al.
Background: Bone-only (BO) metastatic breast cancer (MBC) is considered a more favorable entity than other MBC presentations. However, only few retrospective series and data from selected randomized controlled trials have been reported so far. Methods: Using the French national multicenter ESME (Epidemiological Strategy and Medico Economics) Data Platform, the primary objective of our study was to compare the overall survival (OS) of patients with BO versus non-BO MBC at diagnosis, with adjustment on main prognostic factors using a propensity score. Secondary objectives were to compare first-line progression-free survival (PFS1), describe treatment patterns, and estimate factors associated with OS. Results: Out of 20, 095 eligible women, 5041 (22.4%) patients had BO disease [hormone-receptor positive (HR+)/human epidermal growth-factor-receptor-2 negative (HER2−), n = 4 102/13, 229 (31%); HER2+, n = 644/3909 (16.5%); HR−/HER2−, n = 295/2 957 (10%)]. BO MBC patients had a better adjusted OS compared with non-BO MBC [52.1 months (95% confidence interval (CI) 50.3–54.1) versus 34.7 months (95% CI 34.0–35.6) respectively]. The 5-year OS rate of BO MBC patients was 43.4% (95% CI 41.7–45.2). They also had a better PFS1 [13.1 months (95% CI 12.6–13.8) versus 8.5 months (95% CI 8.3–8.7), respectively]. This observation could be repeated in all subtypes. BO disease was an independent prognostic factor of OS [hazard ratio 0.68 (95% CI 0.65–0.72), p < 0.0001]. Results were concordant in all analyses. Conclusion: BO MBC patients have better outcomes compared with non-BO MBC, consistently, through all MBC subtypes.